Detection and Mitigation from Wormhole Based Protocol Deviation Depends on Neighbor Discovery Approach In WSN - Mandal, Sandip; Sushil, Rama (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks (WSN) are composed of a large ,yet limited number of sensing devices called sensors, communicating over a wireless media. Wireless sensor networks find prospective applications in fields like environmental monitoring, healthcare, battlefield surveillance, and homeland security. A much broader spectrum of future applications is likely to follow. Deployment of WSN in hostile environments, unattended operation, openness of communication and resource constraints e.g. limited memory, energy and computational capabilities exposes WSN to a number of security attacks. The resource constrained nature of WSN makes conventional security mechanisms incongruous to apply. In this paper, an In-Band wormhole attack on a wireless sensor network is studied, in which an adversary creates a link between two regions of the network by using colluding network nodes. The impact of an In-Band wormhole attack on data transmission and energy consumption in the network is studied and a reactive recovery mechanism to detect and mitigate the Denial of Service effect caused due to it is presented.
Keywords: Wireless Sensor Networks; Wormhole; Denial of Service; Routing Attacks; In-Band Wormhole.